FAKTOR RISIKO KEJADIAN DIABETES MELLITUS TIPE II PADA WANITA USIA PRODUKTIF DI WILAYAH KERJA PUSKESMAS PURWOSARI KOTA SURAKARTA TAHUN 2017 - Anggi Putri Aria Gita; Kusuma Estu Werdani (Berita Kedokteran Masyarakat (BKM), 2020)
The prevalence of Diabetes Mellitus Type II has always been increasing in the city of Surakarta. According to the data of the Surakarta Public Health Office (2017), the highest prevalence in 2016 was in the region of Purwosari, in the exact work area of community health center (Puskesmas) which was about 4.62%. The majority of sufferers are the women in childbearing age, so it is risky of causing gestational diabetes mellitus (DM), giving birth to an obese baby, and losing the productive age in their life.  The purpose of this research is to analyze the risk factors and to find out the dominant risk factors which cause the diabetes mellitus type II on the women of childbearing age in the work area of community health center (Puskesmas) Purwosari, city of Surakarta. The type of the research is observational analysis with the design of case control. The subject of this research was taken by using Proportionate Stratified Random Sampling in which the numbers of sample are 150 which consist of 50 samples for the case group and 100 samples for the control group.  The data collecting technique used is an interview using questionnaire to the respondents with respect to the family related DM history, eating pattern, body mass index (BMI) and physical activity.  Bivariate data analysis used is chi-square, and the multivariate is using logistical regression.  The result of the research shows that the factors of DM Type II case risk are physical activity (p= 0,002; OR= 3,269; 95% CI= 1, 533-6,973), family related DM history (p= 0,004; OR= 3,121; 95% CI= 1,425-6,835), eating pattern (p= 0,016; OR= 2,646; 95% CI= 1,200-5,834) and BMI before ailing DM Type II (p=0,008; OR= 2,597; 95% CI=1,273-5,298). The dominant factor that causes DM Type II in this case is physical activity of where people with low frequency of physical activity are risky to ail DM Type II with the probability of 3,3 times higher.